Banks and the economy: Evidence from the Irish bank strike of 1966 - Jason Lennard; Seán Kenny; Emma Horgan (Queen's University Centre for Economic History (QUCEH), 2023)
This paper studies a natural experiment in macroeconomic history: the Irish bank strike of 1966, which led to the closure of the major commercial banks for three months. We use synthetic control to estimate how the economy would have evolved had the strike not happened. We find that economic activity slowed, deviating by 6% from the counterfactual path. Narrative evidence not only supports this finding, but also depicts the struggles of households and firms managing a credit crunch, a liquidity shock, and rising transaction costs. This case study highlights the importance of banks for economic performance.
Keywords: E32; E44; G21; N14; N24; 330; Banks; Ireland; macroeconomy; post-war